Leadership and culture : international perceptions of organizational leadership. - Hedges, Pamela M. (Curtin University, 1995)
This study is a comparative investigation of organizational leadership internationally in Australia, Singapore and Malaysia. The thesis developed is largely based on the "PM" (Performance/Maintenance) model of leadership developed by Misumi over the last three or four decades in Japan.The Misumi model sets a precedent interesting for its Eastern juxtaposition with Hofstede and for the tension it recognizes between behaviours general to all situations of organizational leadership and those which are context-specific. In addition to the focus on this theory in particular, the study examines the relationship of national and personal values to perceptions and interpretation of organizational leadership behaviour. The underlying purpose is to increase understanding of cross-cultural variables in the field of organizational leadership.For its premise, the research undertaken makes the suggestion that leadership behaviours are influenced by national cultural variables and therefore national similarities or differences are, at least to some extent, culturally determined. It is the scope of this cultural imperative which becomes the focus for the thesis. Hypotheses developed, and the data gathered to test them, centre on the perceptions of consistency between organizational leadership in Australia, Singapore and Malaysia.